Creating a Thriving Business : How to Build an Immensely Profitable Business in 7 Easy Steps - Horrigan, George (Morgan James Publishing, 2012)
Most business owners and leaders have expectations for today, hopes for tomorrow and dreams for down the road for their business. They say to themselves, if this is the business I have and that is the business I want, how do I get from here to there? By using a systematic, structured methodology build upon George Horrigan's experience with over 1,200 businesses over the past 17 years, Creating a Thriving Business shows business owners, leaders, and managers how to solve real world problems and get the kind of results they want. By using a proven, practical, and comprehensive methodology that is simple to understand, straightforward, easy to implement, and extremely effective, the reader will be able to achieve the goals for their business in less hours than they are currently spending on their business, thereby turning today's problems into tomorrow's promise. Creating a Thriving Business shows the reader, step by step how to create a successful, thriving, and immensely profitable business by providing an approach that enables them to eliminate the guesswork, trial and error, and uncertainty associated with trying to beat their competition, grow their business and increase its profitability.